PENYULUHAN DAN PELATIHAN PEMBUATAN GULA-GULA JELLY KELOR (GUJEKELOR) PENCEGAH GIZI BURUK (STUNTING) - ,, Faradiba; Syarif, R.A.; Fatira, A.R.; Nabila, R. (Buletin Udayana Mengabdi; Vol 24 No 1 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i01.p12, 2024)
The government program for reducing stunting aims to reduce its occurrence among toddlers and pregnant women. Stunting can result in hindered vertical growth. This occurrence can take either during the prenatal period or within the first five years of the child's life. Moringa leaves possess essential vitamins and minerals that can effectively inhibit stunting in infants by promoting their growth. Moringa leaves are readily accessible in Pucak Village, although they are only consumed in the form of a vegetable. The idea involves transforming Moringa leaves into candy that is both palatable and visually appealing to children. The objective of this activity is to enhance the understanding and skills of the Pucak Village Community in the production of Moringa jelly candy (Gujekelor), which is abundant in nutrients and fiber. Additionally, participants will learn how to package the candy appealingly and hygienically. The service entailed delivering information regarding the nutritional composition and advantages of Moringa leaves, conducting a gujekelor session with the participation of women from the Pucak Maros Village Community, and administering surveys. The questionnaire yielded data indicating a 50% improvement in knowledge regarding the nutritional composition and advantages of Moringa leaves, as well as a 100% enhancement in the ability to produce and package gujekelor. It is anticipated that the community will be capable of manufacturing gujekelor on a small-scale home industry level, thereby mitigating the occurrence of stunting in Pucak Village. Keywords: moringa leaves, stunting, candy, jelly